1991
DOI: 10.1182/blood.v77.7.1607.1607
|View full text |Cite
|
Sign up to set email alerts
|

Amplification by the polymerase chain reaction of hypervariable regions of the human genome for evaluation of chimerism after bone marrow transplantation

Abstract: We combined the polymerase chain reaction (PCR) with oligonucleotide hybridization as a novel and sensitive technique to evaluate posttransplant chimerism. Specific oligonucleotides for hybridization were synthesized homologous to tandemly repetitive core sequences of regions with a variable number of tandem repeats (VNTRs). Polymorphisms at such loci result from allelic differences in the number of repeats. Primers flanking the repeat region of each of the corresponding VNTRs were used for amplification. Reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Since the PCR technique has the potential to detect DNA at the level of a few cells, MCC may be a serious source for misdiagnosis. PCR allows detection of a minor cell population at levels of 0.1%, as demonstrated for evaluation of chimerism after bone marrow transplantation (Ugozzoli et al, 1991). It has been suggested that levels of contamination as little as 1 ml of maternal blood per ml of amniotic fluid could interfere with PCR results (Rebello et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the PCR technique has the potential to detect DNA at the level of a few cells, MCC may be a serious source for misdiagnosis. PCR allows detection of a minor cell population at levels of 0.1%, as demonstrated for evaluation of chimerism after bone marrow transplantation (Ugozzoli et al, 1991). It has been suggested that levels of contamination as little as 1 ml of maternal blood per ml of amniotic fluid could interfere with PCR results (Rebello et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Uncultured amniotic cells present a higher level of maternal contamination than cultured cells (Winsor et al, 1996), while cultured chorionic villi present the highest level of maternal contamination (Saura et al, 1994). However, CVS is still the first choice for prenatal diagnosis in pregnancies at high risk (van den Berg et al, 2000). Therefore, it is obligatory to reveal the potential MCC in fetal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Haplotypes were assigned after examining nine restriction endonuclease sites within the bglobin gene cluster [HincII (e), XmnI (5 0 to G g), HindIII (within G g and A g), HincII (within and 3 0 to b), AvaII (within b), and HinfI (3 0 to b)] [9]. The study of the segregation in the family of four VNTRs (APO B, DXS52, D1S111, and D1S80) was made using a PCR-based methodology [10,11]. False paternity was excluded by using the AmplFSTR 1 Profiler Plus TM (PCR Amplification Kit) according the manufacturer's instructions (ABI Prism 3100 DNA Genetic Analyzer; Applied BioSystems).…”
Section: Methodsmentioning
confidence: 99%
“…These STR loci were chosen on the basis of their high frequency in the population (Edwards et al, 1992). The sequences of primers used in the study have been published by other investigators (Ugozzoli et al, 1991;Anker, Steinbrueck & Donis-Keller, 1992;Kimpton, Walton & Gill, 1992;Sullivan et al, 1993;Edwards & Gibbs, 1994;Hammond et al, 1994;Hochmeister et al, 1994;Kimpton et al, 1994;Walsh et al, 1996;de Weger et al, 2000). Oligonucleotides for PCR amplification were ordered from BioSource INC (BioSource, Rockville, MD, USA).…”
Section: Str-amplification and Gel Analysismentioning
confidence: 99%